Penggunaan metode pembelajaran card sort untuk meningkatkan keterampilan menulis puisi pada peserta didik kelas v sekolah dasar - Ratna Wijayanti; Hartono Hartono; Yulianti Yulianti (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research is to improve the student poetry writing skills through the use of Card Sort method. This is an action classroom research that carried out for three cycles. Every cycle consist of two meeting and four steps there are planning, implementation, observation, and reflection. Technique that used for collect data are observation, interview, test, and documentation. The data validity test technique uses content validity and triangulation. The data analysis technique uses interactive model learning. The result of this research showed that the initial pre-action test score were 62,88 with classical completeness of 23%, increased in the first cycle by 71,8 with classical completeness of 38,46%, then in second cycle it increased to 74,7 with classical completeness of 53,9%, then in third cycle it increased to 76,8 with classical completeness of 80,75%. Referring to the results of this research it can be conclude that the use of Card Sort method can improve the student writing skills in fifth grades students of SDN 2 Ngadirojo Lor Wonogiri academic year 2018/2019.   Keywords: Card Sort, poetry writing skills, Elementary School